Adopting Machine Learning Models for Data Analytics-A Technical Note - Martin, John R; Swapna, S.L; Sujatha, S (International Journal of Computer Sciences and Engineering, 2025)
Data science is the most promising area in computer science today. Data science uses various methods and techniques to deal with large volume of data accumulated day by day. Predictive analytics is the prime concept in data science by processing these large volumes of data to make important predictions. This is being achieved through machine learning family of algorithms. This paper makes a note on the core concept of machine learning and the strategies to adopt suitable machine learning algorithms for the problems in data science. It also reviews different areas of machine learning applications in data science